Peran Layanan Digital BRKS Mobile dalam Meningkatkan Efisiensi Transaksi Perbankan Syariah: (Studi Kasus Bank Riau Kepri Syariah Capem Baserah) - Ocha, Aprika Rosa (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
For banks involved in providing banking services, ensuring customer satisfaction is a critical aspect that should not be overlooked. Consequently, it is essential for banks to enhance the quality of their digital services. This research aims to explore the impact of BRKS Mobile digital services on the efficiency of Islamic banking transactions at Bank Riau Kepri Syariah Capem Baserah. Aquantitative approach was employed in this study. The researchers utilized various data collection methods, including observation, interviews, and documentation. The findings reveal that the availability of BRKS Mobile services facilitates customers in conducting transactions at any location and at any time. Additionally, BRKS Mobile services are user-friendly, as they help reduce costs and save time, thus enabling customers to complete their transactions quickly.